Professional Ethics of Teachers in the Utilization of Educational Technology - Rahma Dzakirah; Muhammad Abuyah Nur Muallif; Riska Latifatul Husna (Al-Ard: Journal of Education, 2026)
This study aims to explain and understand (1) the concept of teacher professional ethics in the use of technology, (2) the principles of professional responsibility and the moral values of teachers, and (3) challenges and solutions in applying teacher professional ethics in the use of technology. This study uses a descriptive qualitative method with a literature study approach. Data was collected from secondary sources, specifically journals published within the last five years (2021-2025) and digital books (e-books). The results show that teacher professional ethics in the use of technology is a set of values, norms, and moral principles that guide teachers in using technology professionally, responsibly, and with a goal-oriented mindset. The professional responsibilities of teachers are based on honesty, integrity, accountability, fairness, and concern for students’ development. The challenges include teachers’ limited digital literacy, minimal understanding of digital ethics, potential misuse of social media, etc. It is concluded that teachers’ professional ethics play a fundamental role in the use of technology in the digital era and serve as an ethical framework that requires teachers to act professionally, responsibly, and in accordance with moral values. Therefore, mastery of technology must be accompanied by ethical awareness so that educational goals can be achieved optimally and meaningfully.